Phenotype of macular corneal dystrophy in Labrador Retrievers: A multicenter study. (30th January 2019) - Busse, Claudia; Kafarnik, Christiane; Linn‐Pearl, Rose; Volmer, Christelle; Matiasek, Kaspar; Premont, Johana E.; Dulaurent, Thomas; Douet, Jean‐Yves; Gilbert, Ida; Jalomäki, Sari; Trost, Katrin; Isard, Pierre‐Francois; et al.
Abstract: Objective: To describe the phenotype of canine macular corneal dystrophy (MCD) including the clinical presentation, multimodal ocular imaging, histopathology, and ultrastructural analysis in ten Labrador Retrievers. Procedure: Multicentered data collection. Results: Labrador Retrievers affected by MCD were presented between the age of 4.5 and 6 years of age with a history of cloudy eyes and/or visual impairment. Findings on ophthalmic examination included a diffuse haze of the corneal stroma and multiple, well‐demarcated, off‐white to yellow‐brown, punctate corneal opacities heterogeneous in size. Corneal vascularization developed in most dogs as the disease progressed. Disease progression was associated with increased density of the corneal haze as well as increased number and size of the focal opacities and dogs developed significant visual impairment. Spectral domain‐optical coherence tomography revealed multifocal hyper‐reflective regions within the stroma. In vivo confocal microscopy revealed marked alterations in reflectivity throughout the entire stroma. Normal keratocytes could not be identified in affected areas. Histopathology showed stromal collagen fibers separated by acidophilic granular material on hematoxylin and eosin stain. The material stained with periodic acid‐Schiff and colloidal iron stain but not with Masson trichrome stain, confirming the accumulation of glycosaminoglycans. On electron microscopic ultrastructural examination, keratocytes presented with vacuolated rough endoplasmic reticulum and multiple electron dense cytoplasmic inclusions. In areas keratocytes appeared ruptured, with cell organelles and proteinaceous material grouped together between collagen fibers. Conclusion: MCD in Labrador Retrievers has similarities with the human counterpart of the condition and is an important differential diagnosis in dogs with corneal disease.